PENERAPAN MEDIA PEMBELAJARAN WOR PENERAPAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI KELAS VII SMP MUTIARA SINGARAJA : PENERAPAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI KELAS VII SMP MUTIARA SINGARAJA - Komang Meldiawan; Komang Tari Karismayanti; Ni Nyoman Suastini (STKIP AGAMA HINDU SINGARAJA, 2026)
Based on interviews and initial observations, the activity and learning achievement of grade VII students at SMP Mutiara Singaraja in the subject of Hindu Religious Education and Character Education are still relatively low, as evidenced by the pre-test results with a class average of 60,62, a comprehension rate of 60,62%, and a classical completeness rate of only 25%. This study aims to improve student activity and learning achievement through the application of Wordwall learning media. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which is conducted in two cycles, starting from the planning stage, implementation, observation, and reflection. The subjects of the study are 16 Hindu students in grade VII. Data collection techniques include observing learning activities, testing learning outcomes, interviews, and documentation, which are analyzed using Qualitative descriptive analysis assisted by quantitative descriptive analysis. The results of the study indicate that in cycle I, student learning activity reached 62,7%, the average post-test score was 73,12, the classical comprehension rate was 73.12%, and the classical completeness rate was 62,5%, which is categorized as low. In cycle II, the average classical activity of students increased to 82,9%, and the average post-test score increased to 84,06, with a classical comprehension rate of 84,06% and a classical completeness rate of 81,25%, which is categorized as high. Thus, the application of Wordwall media is effective in improving the activity and learning achievement of grade VII students at SMP Mutiara Singaraja in the 2024/2025 academic year. Keywords: Wordwall, Learning Activity, Learning Achievement, Hindu Religious Education